Contribution of the Solvent Extraction Method for Phenolic Compounds, Flavonoids, and Fucoxanthin to the Antioxidative Properties in Extracts of Chaetoceros tenuissimus Meunier - Rattanachitthawat, Napapat; Kanokrung, Amornrat; Rattanachitthawat, Sirichet; Thumanu, Kanjana; Tanthanuch, Waraporn; Machana, Kwanchayanawish (Trends in Sciences, 2022)
Chaetoceros sp. has been found to possess significant amounts of valuable fucoxanthin, phenolics, and flavonoids, with enormous nutraceutical and antioxidant potential. The aim of this study was to employ ultrasound-assisted extraction to determine the antioxidant properties of extracts prepared from Chaetoceros tenuissimus using different solvents: Propylene glycol (PG), acetone (AC), and methanol (ME), with difference ultrasonication times (15 and 30 min). The total phenolic (TPC), flavonoid (TFC), and fucoxanthin (FUC) contents were evaluated. Antioxidant capacity was evaluated by DPPH and ABTS radical-scavenging assays and lipid peroxidation by TBARS. The FUC content was analyzed by HPLC-DAD. 30-min PG extract (PG-30) exhibited the highest TPC (2.75 ± 0.14 mg GAE.g−1 DW), and FUC (8.76 ± 0.06 mg FUC. g−1). Concerning total antioxidant capacity, PG-30 was the most effective against DPPH• (IC50 = 970.19 ± 7.70 µg. mL−1) and TBARS (IC50 = 717.05 ± 1.45 µg. mL−1), while 15-min PG extract (PG-15) presented the highest inhibitory activity against ABTS+• (IC50 = 150.02 ± 6.95 µg. mL−1). The study findings demonstrate that PG extracts of C. tenuissimus exhibit high potential antioxidant activity, likely associated with their content of FUC and phenolics, and could be used in cosmetic preparations and as phytonutrients. HIGHLIGHTS Chaetoceros tenuissimus Meunier from Chonburi province, Thailand High antioxidant activities of tenuissimus extracts by ultrasound assisted extraction with different solvents The correlation between chemical substances content and antioxidant activity GRAPHICAL ABSTRACT